1998
DOI: 10.1046/j.1365-2109.1998.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding Spirulina platensis on the growth, proximate composition and organoleptic quality of common carp, Cyprinus carpio L.

Abstract: The effect of feeding Spirulina platensis on the growth, carcass composition, organoleptic quality, digestive enzyme activity and digestibility of common carp, Cyprinus carpio L., was studied through a culture trial lasting 120 days. Four experimental diets were employed by replacing fish meal protein from the standard diet at 25%, 50%, 75% and 100% through the incorporation of Spirulina. Another diet with Spirulina as the sole source of protein was also used. The final weight gain, specific growth rate, food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
50
2
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 14 publications
9
50
2
1
Order By: Relevance
“…As shown in the previous studies with silver seabream, Siberian sturgeon and red tilapia hybrid (El-Sayed, 1994;Palmegiano et al, 2005;Ungsethaphand et al, 2010). However, the results of some other studies revealed significant changes in whole-body crude protein (Nandeesha et al, 2001;Abdel-Tawwab and Ahmad, 2009;Promya and Chitmanat, 2011), crude lipid Nandeesha et al, 1998Nandeesha et al, , 2001Abdel-Tawwab and Ahmad, 2009), ash (Nandeesha et al, 2001;Tongsiri et al, 2010), and moisture contents (Tongsiri et al, 2010;Promya and Chitmanat, 2011) of fish after spirulina administration.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…As shown in the previous studies with silver seabream, Siberian sturgeon and red tilapia hybrid (El-Sayed, 1994;Palmegiano et al, 2005;Ungsethaphand et al, 2010). However, the results of some other studies revealed significant changes in whole-body crude protein (Nandeesha et al, 2001;Abdel-Tawwab and Ahmad, 2009;Promya and Chitmanat, 2011), crude lipid Nandeesha et al, 1998Nandeesha et al, , 2001Abdel-Tawwab and Ahmad, 2009), ash (Nandeesha et al, 2001;Tongsiri et al, 2010), and moisture contents (Tongsiri et al, 2010;Promya and Chitmanat, 2011) of fish after spirulina administration.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, no significant effects have been reported on growth performance in common carp Cyprinus carpio (Nandeesha et al, 1998), catla Catla catla (Nandeesha et al, 2001), Nile tilapia (Ungsethaphand et al, 2010), and a mixed breed catfish (Clarias macrocephalus × Clarias gariepinus) (Burchell) (Promkunthong and Pipattanwattankhul, 2005). Abdel-Tawwab and Ahmad (2009) attributed the growth enhancement of Nile tilapia fed spirulina to improved feed intake and digestibility and suggested that high contents of several nutrients including vitamins and minerals may aid its growth-enhancing effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations